STRATEGY FOR IMPLEMENTING MINIMUM PASSENGER SERVICE STANDARDS AT KAHYAPU FERRY PORT, BENGKULU PROVINCE - Sutrisno, Slamet Prasetyo; Febriansyah, Febriansyah; Setiawan, Hendrik (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2025)
Kahyapu Ferry Port is a pioneering ferry port located on Enggano Island, one of Indonesia's outermost regions. Kahyapu Ferry Port plays a crucial role in supporting the lives of the people and economic activities on Enggano Island. The high demand for ferry transportation by the Enggano Island community demands an improvement in the quality of port services. However, in the field, there are still passenger service facilities that do not comply with government regulations, such as damage to the terminal building area. Based on these conditions, the author conducted a survey of the problems found and conducted an analysis to obtain analytical results and proposed solutions.